Evaluation of Using Preparation Media via LINE OFFICIAL for Receiving Anesthesia on Knowledge and Anxiety in Patients with Same-day Colonoscopy - Wongpanich, Nicharee (Thai Journal of Nursing and Midwifery Practice, 2025)
Abstract: This quasi-experimental research one group pre-posttest design aimed to compare the knowledge and anxiety of patients who were prepared for anesthesia before and after receiving learning media through the Line Official Account (LOA). The sample group consisted of 150 patients who received anesthesia and underwent day colonoscopy at a hospital, during August 2024 to February 2025. The instruments consisted of learning media via the developed LOA channel. Data were collected using a knowledge and anxiety assessment form and tested for validity and reliability. The analysis was performed using descriptive statistics and pair t-test. The results showed that most patients were female, aged over 55, housewives-husbands, graduated below a bachelor’s degree, and had the universal health coverage. After being prepared through the LOA for anesthesia for day colonoscopy, patient’s knowledge was significantly higher than before (p<.05). The anxiety after receiving anesthesia was also lower than before receiving the learning media (p<.05). The patients were most satisfied with the learning media received. Therefore, the learning media through the LOA channel should be used as one method to increase knowledge and reduce anxiety in patients who received anesthesia and underwent a same day colonoscopy. However, further research with a comparison group is recommended.